Rancang Bangun Miniatur Control Room Pada Budidaya Jamur Tiram - Mahmud Idris; Sigit Kurniawan; Rizki Ramadhoni (LPPM Politeknik Jambi, 2022)
This research focuses on the design and control room miniatures to reduce room temperature and increase humidity values in oyster mushroom cultivation. This miniature control room is designed to be able to maintain a temperature of 15-35°C and 50-80% humidity required by oyster mushrooms. In maintaining the temperature and humidity of the cultivation room, a tool is needed in the form of a fog maker and fan as well as a DHT 11 sensor. The DHT 11 sensor detects the temperature and humidity around the room and the cooling fan will be rotated by a DC motor according to the drive signal given by the fuzzy logic controller and the mist maker. functions to produce dew or increase the humidity of the room, the mist maker will be active if the actual value of humidity is below 85%, but if the actual value of humidity is above 85% then the mist maker itself will not be active. In the results of the temperature and humidity experiment for 2 hours, the initial temperature was 29°C and 81% humidity, for the initial temperature set point value was 26°C and 80% humidity.